Inflammation in Adipose Tissue and Fatty Acid Anabolism: When Enough is Enough! - Ortega, F. J.; Fernández-Real, J. M. (Hormone and Metabolic Research, 2013)
Recent findings in adipose tissue (AT) have uncovered negative interactions among obesity, lipogenesis, and fatty acid (FA) storage, perhaps in response to the increased production of proinflammatory cytokines and transcription factors. Emerging evidence highlights that local hypoxia, generation of reactive oxygen and nitrogen species, increased immune cells infiltration and activation, senescence, inflammation, energy consumption, and decreased lipogenesis in the AT are interrelated and may lead to impaired cytokine and hormonal secretion by adipocytes, and ectopic fat deposition in obesity that strengths the increased risk of suffering metabolic disorders in obese subjects. The information summarized in this review attempts to defend the interdependent relationship of these proofs of concept, supporting the idea that “inflamed” and “dysfunctional” AT are synonymous when referring to obesity. This may happen in severe obese subjects with a large and long-lasting fat excess, when fat depots have reached the point in which excessive fat storage, cell density, and diminished oxygen availability promote decreased lipo/adipogenesis and increased lipolysis and FA release. This response may be induced by an important inflammatory component that promotes angiogenesis and insulin resistance, but also by leptin and the increase of T3 in hyperplastic AT.
Keywords: adipogenesis; lipogenesis; obesity; cell senescence; macrophages; lymphocytes; adipokines